2012
DOI: 10.1002/hrm.21487
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity in leadership succession: Preparing for the future

Abstract: The development of gender diversity in leadership positions is a critical need for many companies as they develop strategies for how they will compete in the future. In this article, we test hypotheses about diverse leadership succession, using survey and archival data. Survey data were collected from executives and managers who responded to questions about their succession planning, successors, and the context of diversity in their work environments. Results indicate that the nomination of women as successors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 112 publications
2
49
0
2
Order By: Relevance
“…In the first of these, Virick and Greer (2012) examined the relationship between perceptions of positive diversity climate for women and the likelihood that job incumbents nominate female successors. They found that, among male incumbents, female successors were more likely to be nominated when incumbents perceived the diversity climate for women to be favorable.…”
Section: Table 2 Subfacets and Example Items For The Fairness And Discrmentioning
confidence: 99%
“…In the first of these, Virick and Greer (2012) examined the relationship between perceptions of positive diversity climate for women and the likelihood that job incumbents nominate female successors. They found that, among male incumbents, female successors were more likely to be nominated when incumbents perceived the diversity climate for women to be favorable.…”
Section: Table 2 Subfacets and Example Items For The Fairness And Discrmentioning
confidence: 99%
“…Conversely, the discussion on organizations’ role in promoting gender equality and diversity is now well developed in the Western context (Alvesson & Billing, ). Accordingly, sophisticated diversity programs designed to enhance inclusion of women are in the HR repertoire of many multinational organizations (Virick & Greer, ). Thus, there may be a scope for interorganizational and intercultural sharing of good practices in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Defined as "collective perceptions of the extent to which an organization is viewed as having fair employee policies and integrates underrepresented individuals into the work environments" [6], diversity climate can shape the effects of diversity on various organizational performance. For example, a supportive diversity climate is known to reduce in-group bias and social categorization processes, thereby mitigating the negative influence of diversity on performance [8].…”
Section: Diversity Climate For Women and Intent To Staymentioning
confidence: 99%
“…Based on previous research on diversity climate for women [6] [17], two scenarios were developed. Each scenario was written as if it described a fictitious company's working environment.…”
Section: Manipulation Of Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation